Pemanfaatan citra spot untuk mengkaji kemungkinan pengembangan kepariwisataan lingkungan karst=The Possible Application of SPOT Image to Study Karst Environmental Development of Tourism - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
ABSTRACT Tourism is one of the alternatives to apply natural resource potential to increase development, which may consequently increase the local people's income and the revenue of the local government concerned. To support these activities is needed the existence of data and information on tourism including the existence of tourist obejcts with the supporting infrastructure and structure. To obtain and present the der trr conected with tourism are needed fast and reasonable methods, one of which is remote sensing. In this research, whose purpose is to expose and present the data of natural appearances and cultivation found in Tepus County, is used the method of remote sensing with interpretation technique of SPOT panchromatic image, scale 1 : 200.000 and result of enlarged scale 1 : 50.000, recorded in August 1987, and infrared air photographs with flase colour, scale 1: 30.000, photographed in 1981 with the other supporting data The final research result is presented in the form of thematic maps with scale 1 : 30.000, interpretation result of SPOT image and air photographs with the correctness obtained through field test. The method used for this research is to interpret the elements of land form and coverage recorded at the image with the completeness based on the secondary data during the activity of field observation. Analysis is done on these data by approach of possibility of tourism development in the researched area By giving scores to each parameter used, such as, the spread condition of the existing tourist objects, supporting accessibility and facilities, it is expected that adaptation degree can be obtained. The final result obtained shows that some natural appearances and cultivation in the researched area indicates the existence of potential for development